2005
DOI: 10.3162/036298005x201653
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Political Representation: Toward a New Typology

Abstract: The mandate-independence controversy still features prominently in studies of political representation even though the problems with its theoretical foundation and empirical operationalization have long been recognized. This article proposes an alternative typology of modes of representation. By combining type of control (ex ante or ex post) with direction of the interactions (bottom-up or top-down), our study captures the most important aspects of the relationship between voters and representatives. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 18 publications
2
72
0
18
Order By: Relevance
“…Following Andeweg and Thomassen (2005), we operationalized the dimensions defining their typology by using responses to the following questions:…”
Section: Modes Of Political Representationmentioning
confidence: 99%
“…Following Andeweg and Thomassen (2005), we operationalized the dimensions defining their typology by using responses to the following questions:…”
Section: Modes Of Political Representationmentioning
confidence: 99%
“…A representative, by definition, should be both. Accordingly, scholars have developed other theoretical typologies of representation (see, for example, Andeweg & Thomassen, 2005;Mansbridge, 2003;Rehfeld, 2009).…”
Section: Democratic Representationmentioning
confidence: 99%
“…According to role theory, attitudes towards representation, including territorial representation, have an effect on how representatives conceive their mandate and prioritize between different aspects of it (Andeweg and Thomassen, 2005; Blomgren and Rozenberg, 2012). As several studies have shown, the representational roles and the way MEPs engage in various activities in the EP are often related to whom they want to represent (Wessels, 1999;Farrell and Scully, 2007).…”
Section: Focus Of Representation and Role Orientations Of French Mepsmentioning
confidence: 99%